Poet Nirendranath : Outside and Inside of the Poem/ কবি নীরেন্দ্রনাথ : কবিতার বাহিরে ও ভিতরে (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
The current year is the birth centenary of Nirendranath Chakravarty (19 October, 1924-25 December, 2018), who was awarded the Sahitya Akademi Award and other awards. Nirendranath started making rhymes from his childhood. After that Nirendranath continued to practice poetry during his school life and later in his college life. During this period, most of the poems he wrote were rejected by the magazine authority, but he continued his writings. At this time, another literary friend of his, Nani Bhowmik was also struggling for writing. The role of friends in the life of Nirendranath was undeniable. In this context, Nirendranath's poet friend Arunkumar Sarkar has to be mentioned. In fact, due to his sacrifice and effort Nirendranath Chakravarty's first poetry book 'Neel Nirjan' was published by 'Signet' Press. At that time, when Nirendranath Chakravarty's 'existence' depended on poetry, the publication of his first book of poems in the extraordinary role of a friend was a very important event in Nirendranath's poetic career. 'Neel Nirjan', published in 1954 gave Nirendranath Chakravarty recognition as a poet. Along with this book his 'Nakshatra Jayer ​​janya' (May, 1969), ‘kolkatar Jishu’ (1969), 'Ulanga Raja' (July, 1971), 'Kabitar Badole Kabita' (June, 1976), 'Aj Sakale' (November, 1978), 'Jangale Ek Unmadini' (January, 1989), 'Chalisher Dinguli' (January, 1994) etc. about thirty poetry books, one ‘Kabyanatya’ and other poems collectively are four hundred and ninenty three in number. And from there Nirendranath Chakravarty's distinction and establishment as a poet is assured. Nirendranath experimented with the rhythm of poetry. It should also be noted that he never considered poetry as only an illusionary thing. His poems came from real life. And Nirendranath's expertises in language and rhythmic quality have made them outstanding. In this artical we have discussed about Nirendranath Chakravarty’s growth and uniqueness as a poet from the very first beginning of his life.
Keywords: Nirendranath Chakravarty; Poem; Dheu; Ulanga Raja; Batashi; kolkatar jishu; Real life; Kabita-Kalpanalata; Inner Meaning